2021
DOI: 10.1111/nph.17587
|View full text |Cite
|
Sign up to set email alerts
|

Carbon concentration in the world's trees across climatic gradients

Abstract: Wood carbon (C) concentration is a key wood trait that varies widely among tree species, but our understanding of the factors governing this trait is limited, despite reason to hypothesize that wood C varies systematically across environmental gradients. We compiled a novel database of 1145 geo‐referenced wood C observations from 415 species, to elucidate climate correlates of wood C concentrations, and test if these relationships differ across tissue types and major taxonomic divisions (i.e. angiosperms vs gy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…In our study, topographic wetness had no effect on intraspecific variation in WSG and WCC. Our results are consistent with meta‐analysis studies conducted at regional or the global scales, which showed that WCC do not correlate with precipitation regimes (Ma et al, 2018; Paroshy et al, 2021). Thus, our finding suggest that these two wood traits may not well reflect species hydraulic strategies (Fortunel et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In our study, topographic wetness had no effect on intraspecific variation in WSG and WCC. Our results are consistent with meta‐analysis studies conducted at regional or the global scales, which showed that WCC do not correlate with precipitation regimes (Ma et al, 2018; Paroshy et al, 2021). Thus, our finding suggest that these two wood traits may not well reflect species hydraulic strategies (Fortunel et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…By contrast, global variations in precipitation and temperature have no consistent effect on WCC (Ma et al, 2018;Paroshy et al, 2021).…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…"For example, data from trees in boreal vs. temperate forests are now more readily differentiated. Based on this growing literature, in 2022 we published a global database of wood CFs (referred to as the Global Woody Tissue Carbon Concentration Database ([GLOWCAD]), containing more than 3,500 individual species-averaged wood CFs from 864 tree species across all forested biomes, based on data from 112 studies published between 2004 and 2022 (16).Georeferenced data points within GLOWCAD also allow for ner-scale biome and climate disaggregation of wood CFs(21) compared to the IPCC table (2006), including wood CFs for tropical, subtropical/Mediterranean, temperate, and boreal forests (Table 2).…”
mentioning
confidence: 99%